A case with seronegative autoimmune hepatitis: Too often missed or delayed in clinical practice M. Basaranoglu, G. Basaranoglu, Z. Demirkok (Istanbul, TR) - Başaranoğlu M.; Başaranoğlu G.; Demirkök Z. (My University, 2025)
A case with seronegative autoimmune hepatitis: Too often missed or delayed in clinical practice Metin Basaranoglu (Istanbul, TR), Gokcen Basaranoglu (Istanbul, TR), Zeynep Demirkok (Istanbul, TR) Introduction: Autoimmune hepatitis (AIH) is a rare liver disease (0.7 to 2 per 100,000 people) which is characterized by the presence of autoantibodies. However, an average of 10% of AIH cases have autoimmune pathology but lack autoimmune serology. For such seronegative AIH (snAIH) cases, there is currently no established diagnostic algorithm for diagnosis and improper or delayed diagnosis of snAIH and can result in progression to cirrhosis. Here, we present a case with cirrhosis with seronegative autoimmune hepatitis diagnosed by liver histopathology and confirmed by steroid therapy Methods: A 38-year-old male patient presents with abdominal pain and yellowish colour in urine and sclera for the last 15 days. The left abdominal distension has been a complaint for the last 4 months (because of enlarged spleen). He had type 2 diabetes mellitus (DM). The patient’s body mass index (BMI) is 28 kg/m2. An transabdominal ultrasound and a CT scan with contrast showed lobulation of the liver contours, segmental hypertrophy of the left lobe, and atrophy of the right lobe, a portal vein 13 mm and spleen 210 mm with mild ascites in the pelvic area. İn his laboratory tests, the following results were obtained: Hb 12.7 g/dl (lower than normal), PLT: 68.000 (low), and WBCC: 3560 mm3 (low), INR:1.1. Serum levels of ALT: 139 IU/l, AST: 134 IU/l, ALP: 267, GGT: 694 IU/l (all higher than normal). All serology tests were negative for hepatitis B and C, ASMA, AND, LKM-1 and AMA. IgG and IgM were mildly elevated. Gaucher test was also negative. Results: Liver biopsy performed and showed that: cirrhosis (f4 fibrosis), interface periportal and periseptal hepatitis, lymphoplasmacytic necroinflammatory infiltrate, and plasma cell infiltration. Steroid therapy was started with 30 mg/day prednisolone and ursodeoxycholic acid 1500 mg/ day orally. After 30 days, she is on a good condition and normal serum ALT, AST, ALP, and GGT. Discussion/Conclusion: There is no definitive test currently available for the diagnosis of snAIH. The diagnosis of snAIH may be made on the basis of the combination of a hepatic 19 pattern of serum aminotransferases, lack of positive autoantibodies, lack of elevation of total IgG, typical histological findings, immunogenetic background. Typical hepatic features of pathology include cirrhosis (19–83%), interface periportal or periseptal hepatitis (75–83%), lymphoplasmacytic necroinflammatory infiltrate, and plasma cell infiltration (17– 50%). Advanced histological stage (f3, f4) is more commonly seen in snAIH than classical AIH as happened in our case. Three-month treatment trials with corticosteroids should be considered in all patients regardless of the serological findings to further confirm diagnosis in patients with a positive response. We gained improvement on hi general condition and laboratory results.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (Med); Clinical Medicine (Med)